Thermo-Mechanical Energy (JOURNAL OF ADVANCES IN PHYSICS, 2024)
Thermodynamics and mechanics are two highly developed disciplines, which have remained very independent. Some studies link them but they are restricted to very limited aspects, as if trying to maintain the independence between them. In Mechanics, energy is considered a single uniform property represented by a scalar magnitude has limited its study. On the contrary, Thermodynamics analyzes each magnitude separately and links them with already different definitions beforehand, this allows these to be given diverse properties often related to the reference systems and subsequently linked to each other a posteriori without losing their particularities. This can be seen in the definition of internal energy and kinetic energy of the volume of gases; In Mechanics, this separation is not made and therefore it is restricted to considering energy as a scalar. This study defines why energy should be subdivided, what advantage comes from analyzing it in this way, what cases it applies to, what answers are obtained that were not achievable before, and it eliminates contradictions that are generated if it is considered only a scalar. This reasoning also opens the way to the introduction of the concept of entropy in mechanics (more precisely in dynamics), which provides answers to the temporal direction of events and, in this way, the false idea of temporal symmetry in the equations is eliminated and it allows us to see that it is presented this way intentionally as a way to simplify problem-solving.